Identifikasi Upaya Hukum Putusan No.456/Pdt.G/2018/Pa.Gtlo: Studi Kasus Sengketa Ekonomi Syariah - Cahyani, Putri Tri; Sururie, Ramdani Wahyu; Rahmani, Salma (Syekh Ali Hasan Ahmad Addary State Islamic University, 2024)
The rapid development of the Islamic economy in Indonesia has given rise to various legal disputes that require special attention, particularly those related to the execution of mortgage rights in Islamic banking. These disputes are often complex, involving considerations of both Sharia principles and prevailing positive law. This research aims to analyze Decision No. 456/Pdt.G/2018/PA.Gtlo along with its related appeal and cassation decisions, to understand the dynamics and implications of such disputes. A case study approach is employed in this normative legal research methodology, with primary data in the form of court decisions were qualitatively analyzed. The research findings reveal a consistent pattern in court decisions, across the first instance, appeal, and cassation levels, rejecting the lawsuit for the annulment of mortgage execution. This rejection is based on several reasons, including formal defects in the filing of the lawsuit, the prohibition of retrying a case (ne bis in idem), and limitations on the scope of cassation review. These findings emphasize the importance of a deep understanding of the legal procedures applicable to disputes in Islamic economics, especially in the context of mortgage execution. Misunderstanding or negligence in fulfilling legal procedures can have serious consequences, such as the rejection of a lawsuit and losses for the disputing parties. Furthermore, this research highlights the importance of carefulness in filing lawsuits, particularly concerning formal and substantive aspects, to avoid unnecessary retrials.